2021
DOI: 10.1007/s00268-021-06165-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Hepatic Epithelioid Hemangioendothelioma: A SEER Database Analysis

Abstract: Background Hepatic epithelioid hemangioendothelioma (HEH) is a rare tumor that can affect multiple organs. Little is known about the pathophysiology, clinical course and management of this disease. The aim of this study is to determine survival rates and elucidate the role of various prognostic factors and therapeutic modalities as compared to surgery on patients with HEH. Methods A retrospective analysis on patients diagnosed with HEH between 2004 and 2016 was performed utilizing the SEER database. Kaplan–Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In the first study (N=56, period 1973-2014), 1-year overall survival rates were 57% vs. 67% vs. 80% in patients undergoing resection, no surgical approaches, and LT, respectively (31). The more recent analysis (N=79, period 2004-2016) reported 1-and 5-year overall survival of 87% vs. 75% and 61% vs. 37% in the surgical vs. the nonsurgical group, respectively (62).…”
Section: Discussionmentioning
confidence: 99%
“…In the first study (N=56, period 1973-2014), 1-year overall survival rates were 57% vs. 67% vs. 80% in patients undergoing resection, no surgical approaches, and LT, respectively (31). The more recent analysis (N=79, period 2004-2016) reported 1-and 5-year overall survival of 87% vs. 75% and 61% vs. 37% in the surgical vs. the nonsurgical group, respectively (62).…”
Section: Discussionmentioning
confidence: 99%
“…Although, spontaneously tumor regression of HEH was reported, we found that the tumor progressed slowly for most patients ( 3 , 4 , 17 ). Surgical resection has been reported with good long-term results ( 1 , 18 ). However, due to the multiple intrahepatic lesions and extrahepatic metastasis, radical surgery was impossible for most HEH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic epithelioid hemangioendothelioma (HEH) is a very rare tumor originated from vascular endothelial cells, with unpredictable malignancy ( 1 , 2 ). The rarity of the disease limits the implementation of clinical trials and no standard treatment paradigm has been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…While considering the risk of post-transplantation recurrence and the potential indolence of HEH, the value of this procedure has also been doubted recently (7). Surgical resection has also been reported with good long-term results (1,23). However, according to our previous study, surgical resection was impossible for most patients with HEH due to the multiple intrahepatic lesions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic epithelioid hemangioendothelioma (HEH) is an extremely rare tumor that originates from vascular endothelial cells and has unpredictable malignancy (1,2). Due to the rarity of the disease, clinical trials are very difficult to conduct.…”
Section: Introductionmentioning
confidence: 99%